The Monge-Ampère Equation for Strictly $(n−1)$-Convex Functions with Neumann Condition (Journal of Mathematical Study, 2020)
A $C^2$ function on $\mathbb{R}^n$ is called strictly $(n-1)$-convex if the sum of any $n-1$ eigenvalues of its Hessian is positive. In this paper, we establish a global $C^2$ estimates to the Monge-Ampère equation for strictly $(n-1)$-convex functions with Neumann condition. By the method of continuity, we prove an existence theorem for strictly $(n-1)$-convex solutions of the Neumann problems.
Keywords: Neumann problem; $(n−1)$-convex; elliptic equation.